Development and Validation of Endemic Hope Scale - Wajeeha Riaz, Roomana Zeb, Saima Arzeen, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The objective of this study was to construct and validate a culturally and linguistically relevant scale for measuring hope. Method: The researchers used a logical-content approach to generate a pool of 42 items, which were then subjected to qualitative item analysis by an expert in the field. Based on this analysis, 29 items were deemed acceptable and 13 were eliminated due to poor content validity and overlapping content. The remaining items were subjected to quantitative item analysis using the Endemic Hope Scale on a sample of 202 participants between 18 to 32 years (M=22.12, SD=2.09). Along with the current scale two standardized instruments named Adult Dispositional Hope Scale (Synder et al,1991) and the Zung Self Rated Depression Scale (Zung,1967) were administered on the sample in order to establish the convergent validity with the former and discriminant validity with the later. Item total correlation was computed and 10 items had a correlation below 0.30.Thus, they were eliminated from the scale and 19 items were retained. Principal Component Factor analysis was carried out using Oblimin rotation method after the confirmation of the KMO measure which had a value of .87. Findings: The results revealed two factors which explained 39.73 % of the total variance and were labeled as belief specific reliance and universal reliance. The alpha coefficient was .83 which demonstrated high internal consistency, and the scale showed good convergent validity (r = .39) with the Adult Dispositional Hope Scale and good discriminant validity (r = -.31) with the Zung Self Rated Depression Scale. Conclusion: Based on these results, the Endemic Hope Scale is a reliable and valid measure for assessing hope in an indigenous context. Keywords: Hope, belief specific reliance, universal reliance, convergent validity, divergent validity, indigenous measure.